(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
As an important diagnostic device for detecting respiratory infections, the nasopharyngeal swab is running out of supply due to the fast spread of COVID-19. In this short paper, we present a novel design platform in Matlab for realizing patient-specific nasopharyngeal swabs that can be quickly 3D-printed to fill the swabs’ shortage. Firstly, the swab is realized with our geometry modeling tool using the size derived from the patient’s CT data. Then, Selective-Laser-Sintering (SLS) is employed to print the swab using polyamide as biocompatible material. A printed swab is also presented to demonstrate the performance of the proposed design platform.